A novel NKp80-based strategy for universal identification of normal, reactive and tumor/clonal natural killer-cells in blood - Morán-Plata, F. Javier; Muñoz-García, Noemí; González-González, María; Pozo, Julio; Carretero-Domínguez, Sonia; Mateos, Sheila; Barrena, Susana; Belhassen-García, Moncef; Lau, Catarina; Teixeira, Maria Dos Anjos; Santos, Ana Helena; Yeguas, Ana; et al. (Frontiers in Immunology, 2024)
Purpose. NK cells are traditionally identified by flow cytometry using a combination of markers (CD16/CD56/CD3), because a specific NK-cell marker is still missing. Here we investigated the utility of CD314, CD335 and NKp80, compared to CD16/CD56/CD3, for more robust identification of NK-cells in human blood, for diagnostic purposes.Methods. A total of 156 peripheral blood (PB) samples collected from healthy donors (HD) and patients with diseases frequently associated with loss/downregulation of classical NK-cell markers were immunophenotyped following EuroFlow protocols, aimed at comparing the staining profile of total blood NK-cells for CD314, CD335 and NKp80, and the performance of distinct marker combinations for their accurate identification.Results. NKp80 showed a superior performance (vs. CD314 and CD335) for the identification of NK-cells in HD blood. Besides, NKp80 improved the conventional CD16/CD56/CD3-based strategy to identify PB NK-cells in HD and reactive processes, particularly when combined with CD16 for further accurate NK-cell-subsetting. Although NKp80+CD16 improved the identification of clonal/tumor NK-cells, particularly among CD56 -cases (53%), aberrant downregulation of NKp80 was observed in 25% of patients, in whom CD56 was useful as a complementary NK-cell marker. As NKp80 is also expressed on T-cells, we noted increased numbers of NKp80 + cytotoxic T-cells at the more advanced maturation stages, mostly in adults.Here we propose a new robust approach for the identification of PB NK-cells, based on the combination of NKp80 plus CD16. However, in chronic lymphoproliferative disorders of NK-cells, addition of CD56 is recommended to identify clonal NK-cells, due to their frequent aberrant NKp80 -phenotype.